SUPPORT-FREE TECHNOLOGY FOR MAINTAINING SHRUBS OF BLACKBERRY AND DEWBERRY VARIETIES IN THE COLLECTION ORCHARDS OF KRYMSK EXPERIMENT BREEDING STATION OF VIR - V. N. Podorozhnyi (Труды по прикладной ботанике, генетике и селекции)
An algorithm has been developed at Krymsk Experiment Station of VIR to build up and maintain the work with the existing and future collections of berry crops. It incorporates both practical and theoretical activities into the management system, whose ultimate goal is the improvement of cultivars. The studies to optimize the maintenance of blackberry and dewberry collection orchards of VIR resulted in the development of a support-free cultivation technique for trailing blackberry (northern dewberry) accessions. It was proposed to plant them in rows, earlier mulched with a black polymer film resistant to photodecomposition and high solar radiation, one-meter wide, with a pipe buried underneath it for drip irrigation and fertigation through drippers arranged at intervals of 1.1 m. The edges of the polymer film are proposed to be pinned to the ground with metal studs or sprinkled with earth to avoid disturbances of the mulch integrity. The planting pattern for seedlings needs to be denser than the conventional one (with trellises) and is prearranged by digging holes in the mulching film, up to 10 cm in diameter, at intervals of 1.1 m in a row, so that a dripper is placed above the root system. The space between rows is 1.0–1.1 m. In the proposed method, regrown shoots are pruned during the growing season at a height of 80–90 cm. This operation enables fruit buds to develop next year on these shortened shoots and second-order shoots formed upon them, which will also be pruned or nipped at a height of 30–40 cm. After the end of fruiting, such shoots are removed, and those regrown at the base of the shrub are shortened in the same manner as above. This in vivo maintenance technology for trailing blackberry or dewberry accessions preserved at Krymsk Station of VIR was duly tested, and the trials showed its higher efficiency compared with the reference technique involving trellising of preserved plants. When a black polymer film is used at a plantation for mulching, there is no need for herbicides against weeds, which alleviates the pressure of chemicals on the environment and contributes to the greening of an agrocenosis.